The intricate mechanism of PLS3 in bone homeostasis and disease - Zhong, Wenchao; Pathak, Janak L.; Liang, Yueting; Zhytnik, Lidiia; Pals, Gerard; Eekhoff, Elisabeth M. W.; Bravenboer, Nathalie; Micha, Dimitra (Frontiers in Endocrinology, 2023)
Since our discovery in 2013 that genetic defects in PLS3 lead to bone fragility, the mechanistic details of this process have remained obscure. It has been established that PLS3 variants cause syndromic and nonsyndromic osteoporosis as well as osteoarthritis. PLS3 codes for an actin-bundling protein with a broad pattern of expression. As such, it is puzzling how PLS3 specifically leads to bone-related disease presentation. Our review aims to summarize the current state of knowledge regarding the function of PLS3 in the predominant cell types in the bone tissue, the osteocytes, osteoblasts and osteoclasts. This is related to the role of PLS3 in regulating mechanotransduction, calcium regulation, vesicle trafficking, cell differentiation and mineralization as part of the complex bone pathology presented by PLS3 defects. Considering the consequences of PLS3 defects on multiple aspects of bone tissue metabolism, our review motivates the study of its mechanism in bone diseases which can potentially help in the design of suitable therapy.Plastin is an ancient and evolutionarily highly conserved family of actin-binding